Évolution des problèmes liés à la toxicomanie et des politiques relatives aux drogues au Royaume-Uni - Pearson, Geoffrey (Déviance et société, 2008)
Britain was something of a late developer in terms of problems with illicit drugs. The use of opium and morphine in various medicinal products was not unknown in the 19th century, and during the 1914-18 War there was a brief episode of cocaine use. However, after the adoption of the Rolleston committee system in the 1920s, the level of drug addiction remained remarkably low but the so-called «British system» broke down in the late 1960s. Heroin in cheap and plentiful supply became suddenly available from Iran and Afghanistan. The habit of «chasing the dragon» spread like a whirlwind among the young unemployed (this was the Tatcher’s period) in many towns and cities in the north of England. A dominant policy response to this epidemic from the late 1980s onwards was the promotion of «harm reduction» strategies to combat the spread of HIV/AIDS (such as needle exchange schemes). The policy agenda has also shifted, away towards a crime-control approach with one-third or more of crime being estimated to be drug-related, especially to heroin and crack-cocaine. The most commonly used drug in Britain remains cannabis, with probably 3-5 million regular users, and quite recently the penalties for cannabis possession have been reduced; and since then the level of cannabis use has fallen a little. But why is unknown.